Exploring the Antibacterial Potential of 2-Ethylacridine from Salacia chinensis: Insights into its Mechanism against Methicillin-Resistant Staphylococcus aureus (MRSA) - Manju , S.; Jegadeeshkumar , D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a growing health issue in India, leading to higher healthcare costs and increased morbidity and mortality rates. The prevalence of MRSA in both community and hospital settings has been on the rise, necessitating the exploration of alternative treatments. Aim: This study aimed to isolate secondary metabolites from Salacia sinensis and determine their mode of action against MRSA through molecular docking. Methodology: The study involved the collection of plant samples from Tamil Nadu, India, and the extraction of phytochemicals using methanol and chloroform. GCMS analysis was conducted to identify the bioactive compounds, and molecular docking analysis was performed to assess the antibacterial activity of 2-Ethylacridine against the multi-drug resistance protein (nora) of S.aureus. Results: The qualitative phytochemical screening of S. chinensis extracts revealed the presence of proteins, carbohydrates, flavonoids, saponins, sterols, terpenoids, and alkaloids. GCMS analysis identified bioactive compounds namely 2-Ethylacridine and Squalene. Molecular docking analysis demonstrated a high binding affinity (-6.8) of 2-Ethylacridine to the Multi-drug resistance protein (nora) of S.aureus. Implications: The study provides insights into the antibacterial mechanism of 2-Ethylacridine against MRSA, suggesting its potential as a promising antibacterial agent. These findings have implications for the development of novel antibacterial agents targeting multi drug resistance proteins and addressing antibiotic-resistant strains.